TEACHING ENGLISH TO STUDENTS IN THE AGRARIAN SPHERE - Djurayeva Xurshida Alisherovna (Journals Park Publishing, 2023)
An intellectually mature generation that satisfies the criteria for educated, spiritual, sustainable development, and cares for the future of our country must be educated in a modern, developed society. The major objective of teaching a foreign language in the Republic of Uzbekistan is to develop students' communicative skill in that language so they may engage in activities in the everyday, academic, and professional sectors in a multicultural society. This article provides feedback and feedback on teaching English to students in the agrarian sector.
Keywords: agrarian sphere, students, English language, competence, formation, communicativeness, mature specialist, professional activity.